A randomized controlled trial of 25 sessions comparing music therapy and music listening for children with autism spectrum disorder. (November 2020) - Rabeyron, Thomas; Robledo del Canto, Juan-Pablo; Carasco, Emmanuelle; Bisson, Vanessa; Bodeau, Nicolas; Vrait, François-Xavier; Berna, Fabrice; Bonnot, Olivier
Highlights: This study addresses a fundamental and so far unanswered question: is Music Therapy more effective than mere Music Listening for children with Autism? This question is addressed through a study with 36 participants (17 participants in Music Listening group; 19 participants in Music Therapy group) and intervention length of 25 sessions over 8 months. Findings show that music therapy results in greater clinical improvement than simply listening to music for children with ASD. Abstract: Background: Music therapy is based on the use of musical elements by a trained and qualified therapist. Clinical researches have suggested that children with Autism Spectrum Disorders (ASD) may benefit from MT. In this regard, this study examines if MT is more effective than simply listening to music for children with ASD. Method: A 8-month RCT has been carried out comparing music therapy (MT) to music listening (ML) for children with ASD aged from 4 to 7 years old. Thirty-seven participants were randomly assigned to one of the two groups (MT vs. ML). The outcome measures were the Clinical Global Impression (CGI), the Childhood Autism Rating Scale (CARS) and the Aberrant Behavior Checklist (ABC) in each condition (MT and ML). Results: CGI scores decreased more for participants in the MT than in the ML condition. This clinical improvement was associated with an improvement of autistic symptoms on lethargy and stereotypy ABC subscales. Conclusion: Our findings suggest that music therapy is more efficient than music listening for children with ASD. The present study thus supports the consideration of MT as a rightful add-on to ASD healthcare programs.